Nitrogen doping in the carbon matrix for Li-ion hybrid supercapacitors: state of the art, challenges and future prospective. Issue 31 (29th March 2017) - Bokhari, S. W.; Siddique, A. H.; Pan, H.; Li, Y.; Imtiaz, M.; Chen, Z.; Zhu, S. M.; Zhang, D.
Abstract : Li ion hybrid supercapacitors are summarized with an emphasis on the use of nitrogen doped graphene and activated carbons. Abstract : Li-ion hybrid supercapacitors (LiHSCs) have emerged as an extremely attractive energy storage system by combining the prime advantages of Li-ion batteries and supercapacitors. As a common electrode material in both lithium ion batteries and supercapacitors, graphene and activated carbons offer a tunable porous structure with high chemical, thermal and physical stability, which in turn results in excellent electronic conductivity and improved capacity as compared with the other electrodes. Elemental nitrogen doping in graphene and activated carbons is believed to further improve their performance. In this review, the state of the art of hybrid supercapacitors is briefly summarized with an emphasis on the use of graphene and activated carbons. Subsequent doping of graphene and activated carbons with nitrogen in LiHSCs is also emphasized.